KAJIAN EKSPERIMENTAL KUAT TEKAN BETON BENDA UJI SILINDER DIKEKANG DENGAN BAHAN CARBON FIBER WRAP - Immanuel Panusunan Tua Panggabean; Valentana Ardian Tarigan (Universitas Quality, 2019)
Changes in building functions by increasing the number of floors to the top / vertical direction or also called by increasing the number of levels will increase the burden on the pole/ column, and changes by removing one of the pillars to expand the room will add burden to the columns and beams. Impairment of concrete quality after the implementation of structural construction is also a problem that is often encountered in the implementation of construction. Beams, columns, plates are structural elements used to receive and distribute loads. Expenses that are added as a result of changes in the function of the structure, additional load on the building, or not achieving the quality of the concrete plan of the building structure. Stages of testing by forming cylindrical specimens of 15 (fifteen) pieces, with each of 5 (five) specimens carried out without using carbon fiber wrap to represent the conditions of specimens in the field which are below the standard quality plan in this study concrete quality plans carried out using a job mix formula for f'c = 30 MPa, while 10 (ten) other test specimens are carried out by confinement using fiber wrap material. Observations were made by looking at the addition of compressive strength of concrete on the given fiber wrap restraints. Other observations are made by observing the collapse pattern and the mechanism of collapse that occurs with and without the test specimen mounted in restraints. The compressive strength of concrete increased by 54% for typical restraints 1 using standard fiber direction and 23% for typical restraints 2 using the opposite direction of standard fiber. The collapse model of the Test object that is not restrained is by following the standard collapse model in SNI, while the Test object that is restrained experiences collapse after the Carbon Fiber Wrap material is torn due to the addition of compressive load on the Test Object.